One Money, One Market-A Revised Benchmark - Henn, Christian; Eicher, Theo. (Washington, D.C. : International Monetary Fund, 2009)
The introduction of the euro generated substantial interest in measuring the impact of currency unions (CUs) on trade flows. Rose's (2000) initial estimates suggested a tripling of trade and created a literature in search of "more reasonable" CU effects. A recent meta-analysis of this literature shows that subsequent papers quantify CU trade impacts at 30-90 percent. However, most recent studies use shorter time series and fewer countries than Rose in his original work. We revisit Rose's original benchmark, extend the dataset, and address Baldwin's (2006) critiques regarding the proper specification of gravity models in large panels by simultaneously accounting for multilateral resistance and unobserved bilateral heterogeneity. This produces a robust average CU trade effect of 45 percent. Yet, the trade impacts of individual CUs vary substantially and are generally lower than those of preferential trade agreements (PTAs). Our revised benchmark can be used as a yardstick for future studies to delineate how estimates differ due to new data or differences in econometric specifications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet